An analysis of internationalisation strategies adopted by diversified banks : the case of BNP Paribas - Nuutinen, Jonna Linnéa (2023)
Through globalisation it has become increasingly important for banks to develop effective internationalisation strategies to remain competitive in the global market. Therefore, it is important to look at the drivers behind bank’s internationalisation strategies and their effectiveness. This thesis analyses BNP Paribas’ internationalisation strategy through qualitative methods to provide an understanding on how banks expand to new foreign markets. Primary data was acquired by interviewing senior managers from BNP Paribas and further secondary data was used to validate the findings. The thesis studied differences in strategy between well-diversified banks and traditional retail banks, with the aim to understand the drivers behind BNP Paribas’ success in its internationalisation. Specifically, the study finds that cultural similarity of target markets diminishes when studying more diversified banks, shifts in the home market affect foreign expansion, and building home market capabilities is essential before beginning foreign expansion. These findings have important managerial implications and provide practical insights for banks planning to expand internationally and contribute to the academic research on banks’ internationalisation strategies. By carefully considering their unique strengths and weaknesses when developing their internationalisation strategy banks can achieve greater success in the global market.